Tracking ablation and movement of icebergs with time-lapse photography at an alpine proglacial lake in Austria - Felix Bernsteiner; Andreas Kellerer-Pirklbauer; Jakob Abermann; Bernhard Hynek (Arctic, Antarctic, and Alpine Research)
Little is known about the evolution and dynamics of icebergs in alpine lakes. We analyzed the movement and ablation patterns of icebergs at an ice-contact lake at Pasterze Glacier, Austria, using time-lapse images. Iceberg evolution was quantified for two timescales and related to meteorological as well as glacier ablation data from the adjacent glacier tongue. On a multiyear scale, ablation and movement of one iceberg (IB1) was monitored during a twenty-five-month period. On a single-day scale, the movement paths of eighty-four icebergs were tracked over 16 hours. Results for IB1 revealed an average iceberg ablation of 72 mm d−1 from June to September and no winter ablation. Iceberg ablation rates rose over time, explained by a rising surface area-to-volume ratio. Monitoring lake-wide iceberg movement for one day shows that a persistent katabatic glacier wind and a valley wind are the main influences on horizontal iceberg movement. Iceberg velocity is roughly 0.6 percent of the wind velocity. The existence of a wind-driven current on the lake surface is proposed. Sudden changes in movement rates, which are not explained by wind data, suggest that iceberg grounding is common. This study provides insight into iceberg melt rates in the absence of wave erosion.